(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
The concept of disagreement, as well as its antonym consent, originated in philosophy in antiquity. This term was actively used by such ancient thinkers as Socrates and Plato. They used it in their works, analyzing completely new approaches to human existence. For ancient thinkers, "disagreement" is a way to negate previous theories. With the phenomenon known as the "linguistic turn," when there was awareness of the priority of language and an active study of dialogic speech, the topic of disagreement started to be actively investigated in linguistics. The speech act of disapproval was typically examined in publications alongside the speech act of consent [64,14-15]. "The speech act of a negative reaction is a reactive act expressing the speaker’s negative attitude to the interlocutor’s action or statement, which is an informative, evaluative or imperative statement with various emotional shades and has a certain embodiment in speech".